Eating patterns and composition of meals and snacks in elite Canadian athletes - Erdman, K. A.; Tunnicliffe, J.; Lun, V. M.; Reimer, R. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The purpose of this study was to determine the meal- and snack-eating frequency and the nutritional composition of each eating occasion of Canadian high-performance athletes during training. Athletes from 8 Canadian Sport Centres prospectively completed 3-d dietary records including all food, fluid, and supplements consumed. The time of consumption and whether the consumption was a meal or snack were also identified. The dietary records were analyzed for energy (kcal) and macronutrient intake (carbohydrate, protein, and fat) and compared based on gender, age, meal vs. snack, and training vs. rest days. Three hundred twenty-four athletic subjects (64% female and 36% male) completed the study. On average, the athletes ate 4.8 ± 0.8 times daily. Nearly all athletes consumed 3 daily meals of breakfast (98.9%), lunch (97.9%), and dinner (98.7%), with few having snacks: 57%, 71.6%, and 58.1% of athletes consumed an a.m., p.m., and evening snack, respectively. Training-day meal frequency did not differ from that during rest days; however, fewer snacks were consumed on rest days. A.m. and p.m. snacks were consumed significantly more often on training days than rest days. Overall, snacks contributed 24.3% of total daily energy intake. Few dietary variations were discovered between genders, while the youngest athletes (<18 yr) ate less often, especially their morning snack, than the older athletes. In conclusion, Canadian high-performance athletes self-adjusted their energy intakes on training vs. rest days primarily by snacking less and reducing their carbohydrate and protein intakes on rest days, yet they consistently ate regular meals